Aqueous extraction of hydroxychavicol from Piper Betle L. leaves - Pin, K. Y. (2006)
Piper betle L. is locally named as Sirih and Betel in English. It is a native medicinal plant of central and eastern parts of Peninsular Malaysia. The betel plant is an attractive and aromatic creeper with alternate, heart shaped, smooth, shining, and long stalked leaves with pointed apex. Betel leaf is well known for its use as masticatory, which consists of fresh betel leaf, betel nut and slaked lime paste. The phenolic compound, Hydroxychavicol, found in the aqueous extract of betel leaf is reported to exhibit useful bioactivities - anticarcinogenic and antimutagenic. Batch experiments of betel leaves extraction were conducted using distilled water as solvent and under different operating parameters including temperature, duration and ratio of solvent to sample. After freeze-drying, the yield of each experiment was determined and analyzed using High Performance Liquid Chromatography (HPLC) to investigate the effects of operating parameters on the major compound, Hydroxychavicol.